2011
DOI: 10.1002/14651858.cd002008.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advice with or without oral nutritional supplements for disease-related malnutrition in adults

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 155 publications
9
106
2
1
Order By: Relevance
“…The findings of improved nutritional intake and improvement in appetite and emotional status (which are aspects of quality of life) are consistent with a systematic review of the effectiveness of dietary advice in disease-related malnutrition (13) . This review found oral nutritional interventions (dietary advice with or without nutritional supplements) to have no effect on survival either across disease groups or in the subgroup of studies of cancer patients (14) , corroborating similar earlier reviews.…”
Section: Nutritional Care As a Component Of Multimodal Management Of supporting
confidence: 83%
“…The findings of improved nutritional intake and improvement in appetite and emotional status (which are aspects of quality of life) are consistent with a systematic review of the effectiveness of dietary advice in disease-related malnutrition (13) . This review found oral nutritional interventions (dietary advice with or without nutritional supplements) to have no effect on survival either across disease groups or in the subgroup of studies of cancer patients (14) , corroborating similar earlier reviews.…”
Section: Nutritional Care As a Component Of Multimodal Management Of supporting
confidence: 83%
“…Another systematic literature review reported that dietary consultation, either with or without prescription of ONS, improved body weight in malnourished older adults which suggests that the dietetic consultation itself is key to improving nutritional status (Baldwin and Weekes, 2011). Furthermore, efficacy of ONS for community living older adults remains unclear, as has been reported in a metaanalysis (Milne et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition may be caused by a number of factors such as acute or chronic disease, dental and swallowing problems, changes in sensory perception and appetite, loneliness, and difficulties with meal preparation and grocery shopping [2][3][4]. Negative consequences of undernutrition such as loss of weight and lean body mass may improve with energy and protein supplementation, and with dietetic counselling with or without oral nutritional supplements (ONS) [5,6]. ONS are ready-to-drink liquids, creams or powder supplements that contain macro-and micronutrients and are commonly used as a supplement to the general diet if food intake is not sufficient.…”
Section: Introductionmentioning
confidence: 99%